Lichenoindicating assessment of air quality in small and medium-sized towns in southern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The results of the study of lihenoindication surface layers of air in small and medium-sized towns of Kherson region: Berislav, Kakhovka, New Kakhovka are presented. Numeric limits of izotoxic lichen indication zones are calculated and their use during the research of lichen indication urban landscapes of Southern Ukraine is recommended. Species composition of epiphytic lichenobiotic groups from the territory of these towns, which has 43 species, are described. In terms of clean air Index the models of the spatial distribution of izotoxic lichenoindicating zones in these areas are calculated. For comparative analysis of the calculated area of izotoxic zones surveyed ranking of the towns for air quality was held. The highest air quality is in Berislav town, and the lowest is in New Kakhovka. The highest air quality of residential landscapes is in residential districts of Kakhovka town, and the lowest is in residential neighborhoods of New Kakhovka town.
Keywords: lichen indication, urban landscapes, epiphytic lichens, air pollution.